2020
DOI: 10.3389/fneur.2020.00153
|View full text |Cite
|
Sign up to set email alerts
|

Combined Diffusion Tensor Imaging and Quantitative Susceptibility Mapping Discern Discrete Facets of White Matter Pathology Post-injury in the Rodent Brain

Abstract: Early loss of white matter microstructure integrity is a significant cause of long-term neurological disorders following traumatic brain injury (TBI). White matter abnormalities typically involve axonal loss and demyelination. In-vivo imaging tools to detect and differentiate such microstructural changes are not well-explored. This work utilizes the conjoint potential offered by advanced magnetic resonance imaging techniques, including quantitative susceptibility mapping (QSM) and diffusion tensor imaging (DTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 82 publications
1
7
0
Order By: Relevance
“…This gray matter atrophy was unchanged at 180 DPI (Figure 2C). This is similar to the gray matter atrophy reported in the murine controlled cortical impact (CCI) TBI model that produces rapid gray matter atrophy that continued to increase between 14 and 30 DPI and persists at 180 DPI (Mohamed et al, 2021;Soni et al, 2020).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This gray matter atrophy was unchanged at 180 DPI (Figure 2C). This is similar to the gray matter atrophy reported in the murine controlled cortical impact (CCI) TBI model that produces rapid gray matter atrophy that continued to increase between 14 and 30 DPI and persists at 180 DPI (Mohamed et al, 2021;Soni et al, 2020).…”
Section: Discussionsupporting
confidence: 77%
“…In preclinical models, progressive atrophy and neural loss peristed for one year followng fluid percussion injury (Smith et al, 1997). Some rodent TBI models show only transient changes in DTI that return to sham levels after 30 DPI (Soni et al, 2020); others have shown chronic degeneration particularly of white matter (Armstrong et al, 2016; Mac Donald et al, 2007; Mohamed et al, 2021; Soni et al, 2020). In the controlled cortical impact (CCI) model of TBI, increased gray matter atrophy ocurred close to the impact site (Mohamed et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the gray matter, the cn-dentate gyrus, CA1 region (the ipsilateral hippocampus was washed away during brain processing for histology), ipsilateral and contralateral amygdala, cortex, and thalamus were explored. Regions-of-interest were drawn manually on the study-specific template using the Australian mouse brain mapping consortium template ( Watson et al, 2017 ) and the Allen adult mouse brain atlas 3 as a reference ( Soni et al, 2020 ). Diffusion and anisotropy values were extracted from the regions-of-interest and correlated with the measures from immunohistochemistry, namely, phosphorylated tau, microglia, and astrocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Though glia morphologies are exquisitely characterized by histology, the relationship between glia and diffusion parameters remains relatively unexplored. Recently, increased density of activated microglia, a marker of inflammation, has been related to reduced FA in traumatic brain injury (Soni et al, 2020) and, intriguingly, the NODDI dispersion parameter (Yi et al, 2019), which Yi et al argue is a marker for greater hindered diffusion in the extra-cellular space.…”
Section: Validation Of Microstructure Beyond Fiber Orientationsmentioning
confidence: 99%